2010
DOI: 10.1021/es1023724
|View full text |Cite
|
Sign up to set email alerts
|

Biodegradation of RDX and MNX with Rhodococcus sp. Strain DN22: New Insights into the Degradation Pathway

Abstract: Previously we demonstrated that Rhodococcus sp. strain DN22 can degrade RDX (hexahydro-1,3,5-trinitro-1,3,5-triazine) aerobically via initial denitration. The present study describes the role of oxygen and water in the key denitration step leading to RDX decomposition using 18 O 2 and H 2 18 O labeling experiments. We also investigated degradation of MNX (hexahydro-1-nitroso-3,5-dinitro-1,3,5-triazine) with DN22 under similar conditions. DN22 degraded RDX and MNX giving NO 2

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
5
0

Year Published

2011
2011
2021
2021

Publication Types

Select...
7
3

Relationship

1
9

Authors

Journals

citations
Cited by 25 publications
(7 citation statements)
references
References 45 publications
2
5
0
Order By: Relevance
“…Previous reports also indicated no significant C isotopic fractionation during aerobic biodegradation (19). From a mechanistic perspective, the enrichment in 15 N and lack of enrichment in 13 C during aerobic RDX degradation are consistent with the initial enzymatic attack by the P450 XplA enzyme on an NON bond in the RDX structure (47), rather than a COH bond, as has also been postulated (7,48). Consistent 15 N enrichment during aerobic biodegradation by all cultures so far examined indicates that isotopic analysis of N isotope ratios in RDX may be a useful tool to detect aerobic degradation of RDX in situ.…”
Section: Discussionsupporting
confidence: 82%
“…Previous reports also indicated no significant C isotopic fractionation during aerobic biodegradation (19). From a mechanistic perspective, the enrichment in 15 N and lack of enrichment in 13 C during aerobic RDX degradation are consistent with the initial enzymatic attack by the P450 XplA enzyme on an NON bond in the RDX structure (47), rather than a COH bond, as has also been postulated (7,48). Consistent 15 N enrichment during aerobic biodegradation by all cultures so far examined indicates that isotopic analysis of N isotope ratios in RDX may be a useful tool to detect aerobic degradation of RDX in situ.…”
Section: Discussionsupporting
confidence: 82%
“… , Biodegradation under oxic conditions and alkaline hydrolysis pathways have both been suggested to denitrate RDX to a dinitro-1,3,5-triazacyclohex-1-ene intermediate ( 3 in Scheme ). ,,,, While the enzymatic reaction involves oxidation of the methylene carbon, the hydrolysis pathway proceeds as a base-catalyzed deprotonation and elimination of nitrite. These mechanistic differences are also manifested in distinct C and N isotope fractionation behavior, with ε N between −2.1 and −2.4‰ as well as negligible ε C for enzymatic oxidation vs ε N of −7.8‰ and ε C −5.3‰ for the HNO 2 elimination. ,, …”
Section: Introductionmentioning
confidence: 99%
“…Past studies have identified nitrite, NDAB, MEDINA (methylenedinitramine), and formamide to be nitrogenous degradation products of RDX-degradation. 9,11,21,41 These observations indicate metabolites from RDX may be available to bacteria in the soil that did not degrade RDX and may account for the 15 N assimilation by some of the labeled populations identified in our analyses. Thus, although our studies served to confirm the general a Estimated BDs, the G+C content was calculated for the 16S rRNA genes plus the fragment size listed on both sides of the genes.…”
Section: ■ Materials and Methodsmentioning
confidence: 74%